The Relationship of Vitamin D and IL-17 Levels with Disease Severity in Pediatric Tuberculosis Patients - Olivianto, Ery; Mustofa Aidid; Iskandar, Agustin (Trends in Immunotherapy, 2025)
Tuberculosis (TB) remains a significant global health burden, particularly in children, where immune responses play a crucial role in disease progression. The objective of this research was to analyze the relationship of vitamin D and IL-17 levels with the severity of pediatric TB. This observational analytic study was conducted at Dr. Saiful Anwar Hospital, Malang, involving 33 pediatric patients diagnosed with TB, divided into mild (n = 8), moderate (n = 18) and severe (n = 7) groups. Severity was determined using the score developed in this study. Vitamin D levels were measured using the Cobas c501 analyzer, and IL-17 levels were measured using the Human IL-17 ELISA Kit. While Vitamin D level was significantly lower in microbiologically confirmed patients (p = 0.038), it was not significantly different among severity groups (p = 0.799). Meanwhile, IL-17 levels were significantly higher in patients with more severe respiratory distress (p = 0.01), although the difference between severity groups was not statistically significant (p = 0.966). Furthermore, there was no correlation between vitamin D levels and IL-17 levels (r = 0.178, p = 0.322). These findings indicate the need for further research to explore vitamin D supplementation as an adjunctive therapy and to evaluate IL-17 as a biomarker for disease activity.